Civil control in local government: theory and practice - Смоляр, О. А. (Problems of legality, 2014)
This article discovering in systematic way analysis of the theoretical and practical aspects of civil control in local government, the problems of monitoring the activities of agencies and local government officials, also author proposed areas of improvement of legal regulation of relations in this area.